Efforts to Improve Religious Understanding of Islamic Education Study Programs’ Students Graduated from Public Schools - Ikramina, Mahreshaibati Bilqis; Sya’bana, Rizqi Putra; Ainuri, Ahmad Fahri Yahya; Ainuzzahro, Mayada (Jurnal Al Maesarah, 2025)
This study explores the impact of limited Islamic Religious Education (IRE) lesson hours in public schools on the religious understanding of students enrolled in the Islamic Education Study Program at UIN Walisongo Semarang. Students from public school backgrounds often encounter difficulties in comprehending complex religious materials at the university level, especially those related to Arabic texts and classical Islamic sciences. Employing a descriptive qualitative approach, the research involved eight participants selected for their academic challenges in adapting to religious learning. Data were collected through interviews, observations, document analysis, and literature studies. The findings highlight the existence of a significant gap in religious knowledge between public school graduates and their peers from madrasahs or Islamic boarding schools. To overcome this, various support strategies were identified, including religious student activity units, Arabic enrichment programs, guidebooks, mentoring systems, and inclusive teaching methods. The study emphasizes the importance of collaborative efforts between lecturers and institutions to provide an inclusive and adaptive learning environment. These interventions aim to strengthen students' religious competence and ensure equal opportunities for academic success in Islamic higher education.